Preface: Refereed Proceedings Tropics of the Imagination Conference 2015 - Stephen Torre (eTropic: electronic journal of studies in the tropics, 2016)
The papers presented in this edition of eTropic were originally delivered at the fifth biennial Tropics of the Imagination Conference held at the Cairns Institute of James Cook University on Thursday 17th September 2015. The conference was open to researchers and postgraduate students with an interest in culture and creativity in the tropics, and to individual artists and arts workers in the field as well as those employed in creative industries. Members of the general public with an interest in these fields also attended.